Volatilomes reveal specific signatures for contamination of leafy vegetables with Escherichia coli O157:H7. (April 2023) - Sousa, Maria; Mulaosmanovic, Emina; Erdei, Anna Laura; Bengtsson, Marie; Witzgall, Peter; Alsanius, Beatrix W.
Abstract: Transmission of foodborne pathogens by plants, especially shiga toxin-producing Escherichia coli, has become a public health concern for ready-to-eat products. Due to the patchy distribution of foodborne pathogens on commodities, random sampling before processing and following packaging cannot reliably exclude presence of pathogenic microbes. Robust, cost-effective, and reliable methods for monitoring pathogenic E. coli on fresh produce are therefore urgently needed. We investigated whether volatile organic compounds are suitable for detection of E. coli O157:H7 contamination of leafy vegetables. Using solid-phase microextraction coupled with gas chromatography-mass spectrometry, we analyzed volatilomes of spinach ( Spinacia oleracea L.) and rocket ( Eruca sativa L.) leaf lysates, and of a common culture medium (lysogeny broth), in the presence and absence of E. coli O157:H7. Volatile profiles varied with the nutrient medium. We found higher proportions of indole, phenylmethanol, 2-methoxyphenol, ethanol, propan-1-ol, decan-1-ol, tridecan-1-ol, nonan-2-one and tridecan-2-one in headspace from inoculated compared with non-inoculated samples. This demonstrates that volatile organic compounds are suitable for detecting contamination of leafy vegetables with E. coli O157:H7. In future work we will focus on adapting the volatile assay for screening for E. coli O157:H7 contamination under different conditions, including intact and damaged baby leaves, leaf packages, or leaf batches, and on increasing its sensitivity. Highlights: Volatilomes are used to detect contamination of E. coli O157:H7. E. coli O157:H7 emits a distinct set of volatiles regardless of the culture medium. Increased release of ketones and alcohols indicates E. coli contamination. Headspace analysis can be developed as alternative monitoring tool.